Nurses’ Perspective On Postpartum Education Needs In A Referral Hospital - Lutfatul Latifah; Nina Setiawati; Aprilia Kartikasari; Hari Siswantoro ((JKG) Jurnal Keperawatan Global, 2022)
Background: The study about nurses’ perception of postpartum complication education is limited. The previous studies in Indonesia focus on providing education as a direct intervention to patients. This study aimed to determine the educational needs of postpartum mothers from the nurses' point of view. Methods: This study was a qualitative study conducted from April to July 2021 in a referral hospital in Central Java, Indonesia. Data were collected through focus group discussions, in-depth interviews, and observations. The participant of this study were seven nurses in the postpartum ward. The collected data were analyzed using a tabulated theme conducted through the thematic analysis approach. Results: All the participants were females. Three major themes were generated in this study: reasons for the need for continuous postpartum education, obstacles to implementing postpartum education, and expectations of future follow-up care. The subthemes for the first theme are patients readmitted to the hospital, excessive educational topics, short admission time, and high-risk postpartum mothers. While the subthemes for the second theme are time constraints, limited educational media, and environmental and cultural influences, and the subthemes for the third theme are continuous monitoring and accessibility of educational media. Conclusion: The study has provided new insights regarding the continuity of postpartum education and the obstacles nurses face and has implications for developing a system of continuity of care for postpartum patients, especially for high-risk patients.